Geminivirus Resistance: A Minireview - Beam, Kayla; Ascencio-Ibáñez, José Trinidad (Frontiers in Plant Science, 2020)
A continuing challenge to crop production worldwide is the spectrum of diseases caused by geminiviruses, a large family of small circular single-stranded DNA viruses. These viruses are quite diverse, some containing mono- or bi-partite genomes, and infecting a multitude of monocot and dicot plants. There are currently many efforts directed at controlling these diseases. While some of the methods include controlling the insect vector using pesticides or genetic insect resistance (Rodríguez-López et al. 2011), this review will focus on the generation of plants that are resistant to geminiviruses themselves. Genetic resistance was traditionally found by surveying the wild relatives of modern crops for resistance loci; this method is still widely used and successful. However, the quick rate of virus evolution demands a rapid turnover of resistance genes. With better information about virus-host interactions, scientists are now able to target early stages of geminivirus infection in the host, preventing symptom development and viral DNA accumulation.